2008
DOI: 10.2147/vhrm.2008.04.01.177
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of calculated future cardiovascular disease by monocyte count in an asymptomatic population

Abstract: Introduction:Although atherogenesis is clearly entwined with systemic infl ammation, the risk-predictive relationship between preclinical and overt cardiovascular disease (CVD) and systemic white blood cell (WBC) subtypes remains unclear. Implication of an association would greatly facilitate cardiac risk prediction, assessment and monitoring. Methods: 1383 asymptomatic individuals (795 men, 588 women) attending for executive health screening were examined clinically as well as with phlebotomy and exercise str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 53 publications
1
20
0
2
Order By: Relevance
“…HDL-C has been associated with monocyte count in studies one third to one fifth the size of the present study, both in healthy individuals and in subjects with the metabolic syndrome. 44,45 The present much larger study extends this primary observation to a new population, demonstrating that HDL-C plays an important role in the monocytosis of individuals with mild renal dysfunction measured by cysC. We additionally showed that AA metabolites tied to low HDL-C and insulin resistance 23 were associated with monocytosis and demonstrated a strong relationship of monocyte count with carotid IMT, which substantially implicates the present findings in atherogenesis.…”
Section: Discussionsupporting
confidence: 79%
“…HDL-C has been associated with monocyte count in studies one third to one fifth the size of the present study, both in healthy individuals and in subjects with the metabolic syndrome. 44,45 The present much larger study extends this primary observation to a new population, demonstrating that HDL-C plays an important role in the monocytosis of individuals with mild renal dysfunction measured by cysC. We additionally showed that AA metabolites tied to low HDL-C and insulin resistance 23 were associated with monocytosis and demonstrated a strong relationship of monocyte count with carotid IMT, which substantially implicates the present findings in atherogenesis.…”
Section: Discussionsupporting
confidence: 79%
“…Outside of schizophrenia in the general population, total WBC (Orakzai et al, 2007; Park et al, 2010; Spencer et al, 2007) and monocyte (Waterhouse et al, 2008) counts, as well as C-reactive protein levels (Choi et al, 2004; Park et al, 2010), have been associated with cardiovascular disease risk. In the Framingham Offspring study, increased total WBC counts were associated with incident atrial fibrillation (Rienstra et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Par ailleurs, selon une autre étude [80], le taux des monocytes sanguins, acteurs importants de l'immunité innée, est corrélé à l'IMC ainsi qu'au taux des triglycérides. Cela concerne les deux sous-populations CD14 dim /CD16 + et CD14 + /CD16+ ; les monocytes CD16 + , contrairement aux CD16 -, stimulent la sécrétion du TNF␣ (pro-inflammatoire) et inhibent celle de l'IL-10 (antiinflammatoire) ; leur taux diminuerait lors d'une perte de poids [81].…”
Section: Le Phénotype Lymphocytaire Et Les Monocytesunclassified